The refuge of affections : family and American reform politics, 1900-1920 - Rauchway, Eric. (New York : Columbia University Press, 2001)
The Progressives-those reformers responsible for the shape of many American institutions, from the Federal Reserve Board to the New School for Social Research-have always presented a mystery. What prompted middle-class citizens to support fundamental change in American life? Eric Rauchway shows that like most of us, the reformers took their inspiration from their own lives-from the challenges of forming a family. Following the lives and careers of Charles and Mary Beard, Wesley Clair and Lucy Sprague Mitchell, and Willard and Dorothy Straight, the book moves from the plains of.
Frontmatter -- Contents -- Aknowledgments -- Abbreviations and manuscript citations -- Introduction -- 1. Dorothy Whitney and Willard Straight -- 2. Mary Ritter and Charles Beard -- 3. Lucy Sprague and Wesley Clair Mitchell -- 4. War and the Progressive Family -- 5. The Narrative of Progress versus the Logic of Events -- Epilogue: The Rise and Fall of The Rise of American Civilization; or, A Further Parable on the Narrative of Progress and the Logic of Events -- Notes -- Works cited -- Index.
Includes bibliographical references (pages 219-229) and index.
Print version record.
JSTOR
Keywords: Social reformers -- United States -- Biography; Families -- United States; Progressivism (United States politics); Réformateurs sociaux -- États-Unis -- Biographies; Familles -- États-Unis.; Progressisme -- États-Unis.; SOCIAL SCIENCE -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; HISTORY -- United States -- 20th Century; Families; Progressivism (United States politics); Social reformers; United States; Familie; Sozialreformer; Progressismus; USA; Sociale verandering; collective biographies; Biographies; Biographies; Biographies